Strategi Membangun Jaringan Bisnis Dengan Pemasok Bahan Baku Produk Fruit Sandwich - Dara Triandini; Elsa Ashaq Alfarizi; Ervina Citra Z; Resya Dwi Marselina (Pusat Riset dan Inovasi Nasional, 2024)
In the age of globalization and intensifying business competition, the endurance of a business heavily relies on its capacity to establish and sustain an efficient business. The purpose of business networking is to expand professional networks, obtain information and resources, and support overall business growth and development. This becomes crucial, especially for businesses engaged in the food industry, where the quality and availability of raw materials play an important role in determining the success of the final product. One product that is increasingly in demand is Fruit Sandwich, a culinary innovation that combines the flavors of fresh fruit with the concept of a practical and nutritious sandwich. Fruit Sanwich is a typical Japanese sandwich that is currently viral and has become a favorite of many people lately. To produce high-quality products, companies need to establish close cooperation with raw material suppliers. The research employs a descriptive qualitative method, aiming to present a descriptive overview of the strategy in establishing a business network with suppliers of raw materials for fruit sandwich produkcts. The research data collection technique includes observation which is a literature study that uses journals as the main object and produces fruit sandwich products. This study aims to determine the business network, production process, marketing, and finance of fruit sandwich products. The results showed that the business network carried out by this fruit sandwich is in the form of a cooperation network with several raw material suppliers such as quality fruits and bread. the production process carried out still uses simple tools, Fruit sandwich marketing is still carried out by relying on word of mouth only, and the monthly profit generated from this Fruit sandwich business is Rp. 13,663,000, with a profit percentage of 37%.